The Effect of Environmental Concern, Attitude, Green Brand Knowledge, Green Perceived Value on Green Purchase Behavior with Green Purchase Intention As A Mediating Variable on Green Beauty Products - Clarissa Vania; Tommy Setiawan Ruslim (Universitas Mercu Buana, 2023)
As time goes by, the beauty industry continues to develop, such as the idea of sustainable beauty. Therefore, it is important for brands to increase consumer purchases in order to compete. The purpose of this study is to examine the effect of environmental concern, attitude, green brand knowledge, green perceived value on green purchase behavior with green purchase intention as a mediating variable on green beauty products. The sample in this study amounted to 236 respondents who were collected with purposive sampling technique to consumers of “TBS” products in Jakarta. Testing the research hypothesis was carried out using the PLS-SEM method. The results of this study indicate that environmental concern, attitude, green brand knowledge, green perceived value have a positive and significant influence on green purchase intention. Green purchase intention was found to have a positive and significant influence on green purchase behavior. In addition, green purchase intention can also positively and significantly mediate the influence between environmental concern and attitude towards green purchase behavior on green beauty products.